Clostridioides difficile incidence related to in-hospital cephalosporin use: a tale of two highly comparable hospitals. (25th October 2018) - Karp, Johan; Edman-Wallér, Jon; Toepfer, Michael; Lundqvist, Anders; Jacobsson, Gunnar
Abstract: Background: Antibiotic treatment is a well-known risk factor for healthcare facility-associated Clostridioides ( Clostridium ) difficile infection (HCF-CDI). Antibiotic stewardship programmes (ASPs) targeting high-risk antibiotics have been shown to decrease HCF-CDI incidence. HCF-CDI incidence is high in Nordic countries despite relatively low antibiotic use in hospital. Objectives: To determine if HCF-CDI incidence was modified by a hospital ASP that restricted cephalosporin use. Methods: The effects of an ASP on HCF-CDI incidence were evaluated in a two-centre setting using a retrospective design. We exploited a strategy of both individual case ascertainment based on chart reviews and aggregated data from the hospitals. Cases were attributed to the antibiotics given prior to disease onset, in proportion to the number of DDDs used. Three periods were studied: 2007 (before the ASP), 2012 and 2015. Results: At the ASP hospital, cephalosporin use decreased by 87% and the number of HCF-CDI/1000 hospital admissions decreased significantly from 2.25 (2007) to 1.16 (2015) ( P  =   0.0014). The corresponding results at the non-ASP hospital showed a non-significant increase from 2.09 to 2.38. A high number of cases could be attributed to cephalosporins at both hospitals. The increased use of other broad-spectrum antibiotics, e.g. piperacillin/tazobactam, at the ASP hospital was not associated with offsetting increases in attributable HCF-CDI cases. Conclusions: Decreased use of cephalosporins is an effective strategy to decrease HCF-CDI incidence over time in a setting with high incidence and low antibiotic use.